Gospel of Joseph (I. Brodsky’s poem “Gorbunov and Gorchakov”) - O. V. Bogdanova (Научный диалог, 2021)
The article traces the intertextual layers of I. Brodsky’s poem “Gorbunov and Gorchakov” (Shakespeare, Goethe, Dante, A. Chekhov, L. Andreev, M. Bulgakov, etc.), establishes a connection with the sacred texts of the Old and New Testaments. The hidden disciple (apostolic) plot is revealed and, as a result, a different arrangement of characters is proposed than is traditionally accepted in Russian studies: the heroes Gorbunov and Gorchaks are considered not as opponentsantipodes, but as heroes closely connected, in particular, by the relations of the teacher and the follower. The three-part (conditional) composition of the poem, focused on the three days and three nights depicted in the text, with its symbolic trinity emphasizes the progressive apostolic path of Gorchakov and emphasizes his special role in the fate of Gorbunov (after L. Andreev, not Judas the traitor, but Judas the disciple). The inner “follower” layer of the poem allows Brodsky to move to the archetypal plot, metaphorizing details and symbolizing situations, translating them to a higher level, saturating them with a capacious philosophical and poetic meaning. The well-thought-out chronotopic structure of the poem — Easter Eve, Holy Week, madhouse — is based on complex allusions and the “internal semantics” of the sign, number, and letters. The theological function in Brodsky’s poem is assumed by the Word, the divine Verb.